2020
DOI: 10.1111/jne.12912
|View full text |Cite
|
Sign up to set email alerts
|

Birth signalling hormones and the developmental consequences of caesarean delivery

Abstract: Rates of delivery by caesarean section (CS) are increasing around the globe and, although several epidemiological associations have already been observed between CS and health outcomes in later life, more are sure to be discovered as this practice continues to gain popularity. The components of vaginal delivery that protect offspring from the negative consequences of CS delivery in later life are currently unknown, although much attention to date has focused on differences in microbial colonisation. Here, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 289 publications
(505 reference statements)
0
31
1
Order By: Relevance
“…OXT is a key modulator of mammalian maternal-offspring attachment and social behaviour [12][13][14][15][16]. The OXT system can be activated by stressful and anxiogenic stimuli and acts as key-modulator of the hypothalamic-pituitary-adrenal (HPA) axis [17][18][19]. Consistent with the important role of OXT in social behaviour promotion and stress regulation, OXT dysregulation has been associated with anxiety and autism spectrum disorders (ASD) [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…OXT is a key modulator of mammalian maternal-offspring attachment and social behaviour [12][13][14][15][16]. The OXT system can be activated by stressful and anxiogenic stimuli and acts as key-modulator of the hypothalamic-pituitary-adrenal (HPA) axis [17][18][19]. Consistent with the important role of OXT in social behaviour promotion and stress regulation, OXT dysregulation has been associated with anxiety and autism spectrum disorders (ASD) [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Given the lag between stimulus onset and c-Fos protein accumulation 17,18 , the activation we observed at 3 h postnatal was presumably triggered by stimuli associated with birth or the immediate peripartum period. A vaginal birth is a complex stimulus involving marked hormonal changes associated with labor, mechanical stimuli associated with uterine contractions, passage through the birth canal, and exposure to the ex utero environment 28 . All of these factors, with the exception of exposure to the ex utero environment, are altered following a C-section delivery.…”
mentioning
confidence: 99%
“…Oxytocin surge during vaginal birth is able to promote GABA switch in the neonatal mouse brain, a crucial maturational event, which can influence the life course trajectory (typical versus pathological), as shown by Tyzio et al. (2006) (for reviews see Kenkel, 2021; Zinni et al., 2018).…”
Section: Discussionmentioning
confidence: 92%
“…However, previous rat studies reported long‐term effects of C‐section on AMPA, NMDA and kainate receptors, distinct from the effects of hypoxia (El Khodor & Boksa, 2003). As a mode of delivery is increasingly studied as an effect modifier of perinatal risk factors (Kenkel, 2021), our study aimed at verifying the long term effects of either hypoxia or C‐section on a class of receptors that plays a fundamental role in brain and behaviour plasticity with potential repercussion on CNS developmental trajectory.…”
Section: Introductionmentioning
confidence: 99%